Biopebbles: DNA‐Functionalized Core–Shell Silica Nanospheres for Cellular Uptake and Cell Guidance Studies. (9th March 2018) - Leidner, Arnold; Weigel, Simone; Bauer, Jens; Reiber, Jens; Angelin, Alessandro; Grösche, Maximilian; Scharnweber, Tim; Niemeyer, Christof M.
Abstract: The development of a versatile class of silica nanoparticles for cell studies is reported. The particles contain a fluorescent dye‐encoded core and a single‐stranded DNA oligonucleotide‐displaying shell. They are accessible in arbitrary size and color through robust protocols for Stöber‐based colloidal synthesis and sturdy chemical surface functionalization. Silica particles in the size range of 100 nm to 1.5 µm diameter containing fluorescein, Cy3 oder Cy5 dye‐encoded cores are synthesized and functionalized with DNA oligonucleotides. These silica biopebbles are conveniently traceable by microscopy and have a high affinity to live cells, which makes them ideal for cell uptake studies, as demonstrated for MCF7 and A431 cancer cells. The biopebbles can be utilized as building blocks for the self‐assembled formation of arbitrary surface patterns on glass substrates. With these architectures, the privileged internalization of the biopebbles can be exploited for improved adhesion and guidance of cells because the particles are no longer ingested by adhered cells due to their physical connection with the solid support. It is believed that the biopebble approach will be useful for a variety of applications, fundamental studies in cell biology and tissue engineering. Abstract : Similar to stone pebbles on the seabed attracting marine organisms, the DNA‐decorated silica nanoparticles reported here have a high affinity to live cells. This phenomenon can be exploited for cellular uptake studies and cell guidance on microstructured surfaces.